Política educacional, currículo e avaliação: a fala dos professores sobre os impactos da implantação da reforma curricular paulista - Cunha, Adriana dos Santos (2010)
The State Secretary of education of São Paulo presented in 2007 a new curricular proposal for public education, which is part of a larger set of proposals, called Programa São Paulo Faz Escola. Its implementation began in 2008 based on a set of goals to be achieved, among them to improve the quality of student learning, which is to be verified by the IDESP, the index of educational development of the State of São Paulo. This research goal was to understand the impacts produced by this educational reform in the school routine and the understanding of the representation that teachers of the public network have about it. This research was performed through semi-structured interviews and documentary analysis. Categories that served as reference for the analysis of data were: curriculum, school culture, practice and public policy. The results show that the actions of acceptance or resistance of teachers derive more from conditions offered by the school of culture and practice than an effectively understanding of the political significance of reform proposed by the State.